PEMBINAAN IBADAH PADA MAHASANTRI PUTRI MA’HAD AL-JAMI’AH IAIN PONTIANAK - Nelly Nelly; Nora Kasih (IAIN Pontianak, 2020)
Abstract: The guidance of worship for female santri is quite interesting, considering the santri who live in Ma’had Aljamiah IAIN Pontianak come from various educational background ranging from high school, MA, Islamic Boarding School and even SMK. These different educational background,the researcher wanted to explore the methods used by the coaches in Ma’had in coaching the worship of female santri of Ma’had al-jamiah IAIN Pontianak. The goals to determine and describe the development of worship of female santri. Occured from the implementation of religious,guidance, supporting and inhibiting factors of religious guidance of female santri. The focus of the research is how to develop worship in female santri of Mahad Aljamiah IAIN Pontianak,from the implementation of worship coaching, supporting and inhibiting factors for fostering worship in female santri. This research was conducted using using qualitative approach with descriptive methods. The data in this study were collected through interviews and documentation. The data result indicates that the implementation of religious guidance for female santri Mahad Aljamiah is carried out according to the plan. The purpose of fostering worship in female santri is toget closer to Allah, discipline in performing prayers and reciting the Quran and it is hoped that the guidance of such worship can be prevented and avoided from heinous and evil acts. Therefore, in implementation several methods are used including lecture, exemplary, habituation, giving advice, supervising and applying punishment. Supporting factors for internal worship development is willingness and awareness of santri, the quality of the ustadz and ustadzah, peers and absences. For external is the support of students parents. As for the internal inhibiting factors such as laziness and the condition of water in the Mahad and for the externall is the afternoon class schedule. Keyword : The Guidance of Worship, Female Santri.